Legal Protection for Indonesian Citizens as Victims of Manipulative Marriages by Refugees: A Normative Analysis of State Responsibility - Moch Rafi Khadafi; Dudik Djaja Sidarta; Renda Anggraeni (International Journal of Law and Society, 2026)
The phenomenon of marriages between Indonesian citizens (WNI) and refugees represents a complex legal challenge due to the absence of specific regulations governing such relationships. This study examines the legal protection for Indonesian citizens who become victims of manipulative marriages by refugees, employing a normative juridical approach with statutory and conceptual methods. The research analyses primary legal materials, including the 1945 Constitution, Law Number 1 of 1974 concerning Marriage, Law Number 39 of 1999 concerning Human Rights, and Presidential Regulation Number 125 of 2016 concerning the Handling of Refugees from Abroad. The findings reveal that Indonesian national law does not specifically regulate marriages between Indonesian citizens and refugees or asylum seekers, creating a significant legal vacuum (rechtsvacuum) that renders such relationships vulnerable to abuse, violence, and legal uncertainty. Furthermore, the state's responsibility in protecting Indonesian citizen victims of manipulative marriages by refugees has not been optimally implemented, despite constitutional and juridical foundations requiring protection from all forms of violence, discrimination, and exploitation. The study recommends the formulation of specific regulations addressing marriages between Indonesian citizens and refugees, strengthening the role of victim protection institutions, and establishing inter-agency coordination systems, including international organisations such as UNHCR and IOM, to prevent abuse and strengthen law enforcement mechanisms.